Foreign exchange fixings and returns around the clock - Ingomar Krohn; Philippe Mueller; Paul Whelan (Bank of Canada, 2021)
We document that intraday currency returns display systematic reversals around the major benchmark fixings, characterized by an appreciation of the U.S. dollar pre-fix and a depreciation post-fix. We propose an explanation based on constrained intermediation by foreign exchange dealers. Exploiting data from a major inter-dealer platform, we present evidence of an unconditional demand for U.S. dollars at currency fixings. Dealers hedge this demand pre-fix, driving intraday reversals in both over-the-counter and exchange-traded markets. Furthermore, order imbalances in futures markets are not related to intraday reversal patterns, suggesting that the marginal investors in foreign exchange markets are intermediaries.
Keywords: F3; F31; G15; 330; Financial markets; Exchange Rates; Market structure and pricing